Modern applications of 3D/4D ultrasound imaging in radiotherapy - Harris, Emma (Ph. D. in radiation physics); Fontanarosa, Davide; Camps, Saskia; Verhaegen, Frank (IOP (Series). Release 21., 2021)
This is a practical guide to the implementation of 3D/4D ultrasound imaging in radiography. Among its features are the coverage of the technology utilised for ultrasound-guided radiotherapy, clinical need and advantages of using ultrasound. It is a practical guide for users which incorporates implementation, potential errors, uncertainties and training. This is a comprehensive review of the state-of-the-art technologies which also looks at the future direction of this exciting field. Researchers, students, hospital physicists and radiographers will all find this book of use as it guides them through current clinical situation and examines the full potential of ultrasound in radiotherapy. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.